Abiraterone acetate plus Prednisone/Prednisolone compared with Enzalutamide in metastatic castration resistant prostate cancer before or after chemotherapy: A retrospective study of real‐world data (ACES). Issue 1 (27th March 2020) - Das, Prantik; Taylor, Sarah; Price, James; Jones, Michael; Martin‐Fernandez, Cristina; Ali, Akram; Mugunthan, Thangrarajh; Mallik, Chandrani; Ward, Colin
Abstract: Background: Abiraterone acetate combined with Prednisone/Prednisolone (AA+P) and Enzalutamide (ENZ) have proven survival benefit in men with metastatic castration‐resistant prostate cancer (mCRPC) in chemotherapy‐naïve and prior chemotherapy patients. There have been no studies directly comparing the effectiveness of ENZ to AA+P in mCRPC patients. Methods: A retrospective, survival analysis study of 143 real‐world mCRPC patients (90 in AA+P and 53 in ENZ group) was conducted. Patients who started their treatment between February 2012 and May 2016 were included. The primary end point was biochemical progression‐free survival (bPFS). Secondary end points were radiological progression‐free survival (rPFS) and overall survival (OS). Toxicity data were also collected. Data were analyzed using Cox proportional hazards (PH) models, adjusting for covariates: prior radical treatment; Gleason score; prostate‐specific antigen; age; and chemotherapy naïve or not. Results: After median follow‐up of 15 months (interquartile range 7 to 23), 112 events of biochemical progression were observed (71 in AA+P and 41 in ENZ). About 41% in AA+P group and 30% patients in ENZ group received prior chemotherapy. The chance of biochemical progression was significantly lower among ENZ patients than AA+P patients, when adjusting for all covariates in the Cox PH model (hazard ratio [HR] 0.54, 95% confidence interval [CI] 0.35 to 0.82, P = .004). There was a trend implying the chance of rPFS could be higher among ENZ patients than AA+P patients (HR 1.24, 95% CI 0.76 to 2.02, P = .4). There is no difference in OS between ENZ and AA+P patients, when adjusting for all covariates in the Cox PH model (HR 0.91, 95% CI 0.59 to 1.41, P = .7). About 38% of ENZ patients reported fatigue compared to 16% of AA+P patients, while hypertension was reported slightly more in AA+P patients. Conclusions: This study showed a statistically significant difference in bPFS, favoring ENZ, but no significant difference in rPFS or OS.